Ekstraksi KOH Dari Abu Tandan Kosong Sawit Menggunakan Sistem Bertahap Banyak Beraliran Co-Current - Ulima, Riris; Zulfansyah, Zulfansyah; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Utilization of oil palm empty fruit bunches is still limited. One alternative to utilizing oil palm empty fruit bunch is by extracting potassium hydroxide from oil palm empty fruit bunch ash. This research aims to determine the effect of extraction time and temperature using the co-current flow method on potassium concentration. The dry ashes of oil palm empty fruit bunches was sieved with a 100 mesh sieve then extracted using water as a solvent at temperatures of 50°C, 65°C, 80°C and extraction times 30, 60, 90 minutes. The results showed that at an extraction temperature of 80°C and extraction time of 90 minutes, the highest potassium concentration was 6.888 ppm. The concentration of potassium increases with increasing temperature and extraction time. Keywords : ash, co-current, extraction, potassium